2016
DOI: 10.5796/electrochemistry.84.7
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Multiwalled Carbon Nanotube Aqueous Suspension with Surfactant Sodium Dodecylbenzene Sulfonate for Lithium/Sulfur Rechargeable Batteries

Abstract: Due to the hydrophobic nature of multiwalled carbon nanotube (MWNT), sodium dodecylbenzene sulfonate (SDBS) was adopted as a surfactant to synthesize a well-dispersed, homogeneous MWNT aqueous suspension. By simple stirring mixing of the resultant MWNT suspension with nano-sulfur aqueous suspension, a novel porous sulfur/ multiwalled carbon nanotube composite (S/MWNT) was synthesized. This preparation method based on the suspension mixing possesses the advantages of simplicity and low cost. Homogeneous dispers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
4
1
Order By: Relevance
“…To confirm the enhanced electrochemical performances of EDA functionalization-modified RGO, the further comparison among S/GO, S/MWNT, S/RGO, and S/EDA-RGO cathodes of Li-S batteries were carried out and the results are compiled in Table 1 . The electrochemical performances of the S/EDA-RGO composite cathode that was obtained here were better than those of the previously reported results [ 48 , 49 , 50 ]. Overall, this confirmed that EDA functionalization-modified RGO could enhance the electronic conductivity of sulfur cathode and suppress the lithium polysulfides that were dissolved in the electrolyte.…”
Section: Resultscontrasting
confidence: 86%
“…To confirm the enhanced electrochemical performances of EDA functionalization-modified RGO, the further comparison among S/GO, S/MWNT, S/RGO, and S/EDA-RGO cathodes of Li-S batteries were carried out and the results are compiled in Table 1 . The electrochemical performances of the S/EDA-RGO composite cathode that was obtained here were better than those of the previously reported results [ 48 , 49 , 50 ]. Overall, this confirmed that EDA functionalization-modified RGO could enhance the electronic conductivity of sulfur cathode and suppress the lithium polysulfides that were dissolved in the electrolyte.…”
Section: Resultscontrasting
confidence: 86%
“…36) except for the appearance of a high-intensity peak at approximately [26][27] , which corresponded to the (002) peak of CNTs-COOH. 38 Hence, the CNTs@ZIF-67 composite was successfully prepared, and the incorporation of CNTs-COOH did not destroy the crystal structure of ZIF-67.…”
Section: Preparation and Characterization Of Cnts@zif-67compositementioning
confidence: 99%
“…[82] Moreover, the sulfur-CNT interaction can be enhanced by homogeneously dispersing CNTs with sulfur. For instance, instead of physically mixing CNTs with the slurry, the addition of the homogeneously suspended CNTs (usually by the use of a surfactant, such as sodium dodecylbenzene sulfonate [83] or cetyltrimethylammonium bromide [84] ) into the sulfur stock helps create a uniform slurry for cathode fabrication. Moreover, inspired by the concept of sulfur vapor infusion, Guo et al used a thermal treatment to incorporate sulfur species (of small sizes, such as S 6 and S 2 ) into the central hollow space of CNTs through the defective area (i.e., the narrow pores) on the sidewall, and the vaporized sulfur molecules would then be converted back to large-size S 8 while the dissolution of polysulfides was suppressed due to the blocking effect on the liquid electrolytes due to the limited size of the channels.…”
Section: Basics For Cnt/sulfur Cathodesmentioning
confidence: 99%
“…Moreover, the sulfur–CNT interaction can be enhanced by homogeneously dispersing CNTs with sulfur. For instance, instead of physically mixing CNTs with the slurry, the addition of the homogeneously suspended CNTs (usually by the use of a surfactant, such as sodium dodecylbenzene sulfonate [ 83 ] or cetyltrimethylammonium bromide [ 84 ] ) into the sulfur stock helps create a uniform slurry for cathode fabrication. Moreover, inspired by the concept of sulfur vapor infusion, Guo et al.…”
Section: Roles Of Cnts In Lithium–sulfur Batteriesmentioning
confidence: 99%